Answer:
The correct answer is ( B ) 8.
Explanation:
We will first solve the two simultaneous equations for the values of 'p' and 'q' respectively.
Equation No. 1 -
2p + q = 11
Equation No. 2 -
p + 2q = 13
We will make 'q' the subject in Equation No. 1 and substitute the expression for 'q' into Equation No. 2.
Equation No. 1 -
q = 11 - 2p
Equation No. 2 -
p + 2 ( 11 - 2p ) = 13
We will solve Equation No. 2 for the value of 'p'.
Equation No. 2 -
p + 22 - 4p = 13
p - 4p = 13 - 22
- 3p = - 9
p = - 9 ÷ - 3
p = 3
We will substitute the obtain value for 'p' from Equation No. 2 into Equation No. 1 to find the value of 'q'.
Equation No. 1 -
q = 11 - 2 ( 3 )
q = 5
We will substitute the obtained values for 'p' and 'q' from Equation No. 1 and Equation No. 2 into p + q.
= p + q
= 3 + 5
= 8
Therefore:
The correct answer is ( B ) 8.